Identifying drivers for employee engagement: a study on attributes intention to stay at ON semiconductor, Seremban / Nur Hamni Harun - Harun, Nur Hamni (2010)
Increasingly, organizations are becoming aware that engaged employees are fundamental to achieving business success and is a key driver of organizational productivity. Here, the researcher describe what are the factor of achieving true engagement, the researcher also seek want to know why figure of resignation from direct labor was high compare with indirect labor, and to define what attributes can make employees stay in the company. ON Semiconductor was a multinational company where is a preferred supplier of power and signal management products and solutions to customers throughout the world. ON Semiconductor produce semiconductor devices and wafer fab. The researcher interviewed 30 respondents which is all an operator at ON Semiconductor and they still working in this company. The researcher collects the data from interview session, the information also gathers from data record by the company such as employee resignation for 2008 and 2009. Hence, journals, articles and website related to this issue pretty help the researcher to get more information on that. This study explores the factors contributing to an engagement among employees in the organization. It looks at reward and recognition as one of the main thing in order to engage the employees. This research attempts to dissect that communication and organizational culture also and environment of the organization can influence employee engagement. It helps to identify the effect of affective relationship with co-workers and leader on retention among employees. Growth and advancement opportunities offer by the organization may be the basic leads to employee engagement. Through the interview, in term of communication and organizational culture, there is no exposure about internet usage, unconsidered employee opinion / Company do not take action, layoff the family day and less of indoor and outdoor activities, and enough of notice board. For reward and recognition (R&R), R&R can be great motivation to encourage employee, insufficient reward and recognition, unfair of performance appraisal, and respondent highlighted more on worthless reward and overtime (OT) payment during festive season not standardize. For Career Growth Opportunities, the output were no career growth, the material for training not organize well (Orientation), and lack of training for operator. When talk about relationship at work, no proper coaching and mentoring be upmost complaint by the respondents, other than that there fewer of direct communication between employee and supervisor and less of kinship (familial) spirit. Through observation on company activities, the researcher thought the company had enough programs to enhance employee engagement but maybe arrangement for the activities were imperfect or unsatisfied. All the factor mentioned are important but the most things hoping by employee is appreciating them by give sufficient reward and concern about their problems. The great company not even has a productive output but has engaged employee who can go extra mile in doing their job. The researcher had recommended the company to communicate realistic job expectations, responsibilities and duties, and reward systems, be open to their ideas and considering employee opinion, expose about internet using, reinstate Family Day and increase recreation activities, appraise fairly and treat people as equals, provide career growth opportunities, be more concern about employee personal matter and listen to what employees have to say, providing coaching and build a mentoring culture, and widen the scope for ONer of The Month. From a practical point of view, organizations can use the results and recommendations of this study to ensure the employee engage with the organization.